Kajian Dugaan Praktik Kartel PT Garuda Indonesia, Tbk Mempengaruhi Pergerakan Harga Saham di BEI - In'am Widiarma; Nenny Syahrenny (Jurnal Ilmu Manajemen, 2021)
The purpose of this study was to determine the effect of the alleged cartel practices carried out by airline X, namely by the increasingly high price of airline tickets and how their impact on the stock price movement itself. This practice is not permitted in Indonesia and almost all countries globally, but this becomes very problematic in the current aviation business. If the ticket price is not raised, the company will bear substantial losses. Still, on the other hand, consumers are significantly disadvantaged and can sacrifice the country's economy if countries that depend heavily on air transportation, such as Indonesia. Considering that airline X is a state-owned company of the Republic of Indonesia listed on the Indonesia Stock Exchange, whether news of alleged cartel practices could affect the public investors in the capital market in deciding to make selling or buying transactions on shares.